The Cost–effectiveness of Varicella Zoster Virus Vaccination Considering Late Onset Asthma. Issue 9 (September 2016) - Ditkowsky, Jared; Kohlhoff, Stephan; Smith-Norowitz, Tamar A.
Abstract : Background: Recent studies reported that infection by varicella zoster virus (VZV) may lead to delayed onset of asthma in children/adolescents. This information will likely alter the cost–effectiveness of the US. VZV vaccination program. We created a decision analysis model to estimate the costs and health-related effects of VZV 2-dose vaccination, assuming VZV infection delays asthma onset. Methods: The Markov model considered a birth cohort of 3, 957, 577 individuals entering the population from a societal perspective. We predicted the number of asthma/VZV cases, asthma-/VZV-related mortality and costs associated with asthma/VZV. Comparison arms included (1) VZV vaccination program without delayed asthma onset, (2) VZV vaccination program with delayed asthma onset and (3) no VZV vaccination program with delayed asthma onset. We considered delayed onset ranging from 3 to 12 years. Results: The vaccination program proved cost–effective without an assumed delay in asthma onset. When the vaccination and no-vaccination arms were compared assuming delayed asthma onset, vaccination remained less costly despite increased savings related to asthma without vaccination. With delayed asthma onset of 9 years post VZV infection, cost savings due to vaccination were $914.09 million, with 9984 cases of asthma averted and 9 greater overall deaths with vaccination. Conclusion: VZV vaccination program was less costly than the "no-vaccination" scenario, despite delayed onset of asthma post VZV infection. However, vaccination resulted in increased asthma morbidity and mortality. This adds to current evidence that VZV vaccination is cost–effective, and may alter asthma-related health-care outcomes. VZV's effect on asthma symptoms still needs further evaluation before firm conclusions can be reached.